Non-equilibrium long-range phase transition in cold atoms : theory and experiment - Mancois, Vincent (Nanyang Technological University, 2020)
We study the long-range force arising from the absorption of non-saturating laser beams in a two-dimensional cloud of cold atoms. The force created by the lasers is attractive and similar to the usual Newtonian gravity along the beam. The cloud is composed of bosonic strontium 88 cooled and trapped on the intercombination line. Transferring the atoms in a two-dimensional optical dipole trap in a magical wavelength configuration, a canonical non-equilibrium phase transition is expected. Below a critical temperature, selfgravitating particles in two dimensions can collapse, nearly by the same mechanism stars are forming. We observed experimentally transient compressions, a halfway satisfactory result originating from the power limitation of our dipole trap. The second part of the thesis focuses on the theoretical realization a minimal Brownian motor within a system of trapped particles in 2D, similarly to our experimental situation. The phenomenon characterizing the Brownian motor is the appearance of a macroscopic current of particles. We have shown that this direct transport of particles is independent of the details of the trapping potential and obtained if and only if two symmetries are jointly broken: By the presence of two heat baths along orthogonal directions together and an anisotropic trap misaligned from the temperature axes.